Равнение на знамя: [роман] / А. Бушков - Бушков Александр Александрович (Читай, Россия!, 2008)
Экземпляры: аб. (20181115) / Инвентарный номер: 58962 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 94 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44